Colloidal Dispersions (Liposomes and Ethosomes) for Skin Drug Delivery and their Role on Rheumatoid Arthritis (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of the present work was to focus on the applicability of liposomes and ethosomes for transdermaldelivery. In the current review, we had focused on transdermal delivery transdermal delivery of vesicular systemvesicular systems, i.e., liposome and ethosomes, factors affecting their permeation and penetration efficiency,limitations, applications, method of preparations, evaluation parameters, and selection of lipids. In this review,we considered the mechanism of controlled drug release of vesicles by transdermal delivery and the impact oftheir physicochemical properties. Rheumatoid arthritis (RA) is most frequently suffering disease in the geriatricpopulation. By transdermal delivery, conventional anti-RA (ARA) therapy associated with several disadvantages.The modern ARA therapy; disease-modifying antirheumatic drugs (DMARDs) are more effective in reducingdown disease progression. The basic mechanism of action of DMARDs in RA is not clear. The vesicles have apotential role in RA; especially, we focused on the impact of liposomes and ethosomes on RA by transdermaldelivery, vesicular mechanism to justification in ARA therapy. Conclusion: The liposomes and ethosomes werebeneficial tools for transdermal delivery. They have a potential role to control RA by transdermal delivery.